2018
DOI: 10.1039/c7dt04372d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the manganese and cobalt content on the electrochemical performance of P2-Na0.67MnxCo1−xO2 cathodes for sodium-ion batteries

Abstract: The resurgence of sodium-ion batteries in recent years is due to their potential ability to form intercalation compounds possessing a high specific capacity and energy density comparable to existing lithium systems. To comprehend the role of cobalt substitution in the structure and electrochemical performance of NaMnO, the solid solutions of P2-NaMnCoO (x = 0.25, 0.5, 0.75) are synthesized and characterized. The XRD-Rietveld analysis revealed that the Co-substitution in NaMnO decreases lattice parameters 'a' a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 60 publications
1
20
1
Order By: Relevance
“…[99] Higher diffusion coefficient values are observed in the main Co 3+ /Co 4+ redox couple with increased Co content. [103] The sodium ion diffusion during cycling is also more complex than other P2-type systems previously studied, involving a cooperative mechanism. [104] Summarizing the aforementioned results, it is possible to both improve the Na + kinetics and achieve more stable P2 structures via introducing an appropriate amount of Co into the P′2-Na x MnO 2 compounds with the sacrifice of some specific capacity as well as rate capacity.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…[99] Higher diffusion coefficient values are observed in the main Co 3+ /Co 4+ redox couple with increased Co content. [103] The sodium ion diffusion during cycling is also more complex than other P2-type systems previously studied, involving a cooperative mechanism. [104] Summarizing the aforementioned results, it is possible to both improve the Na + kinetics and achieve more stable P2 structures via introducing an appropriate amount of Co into the P′2-Na x MnO 2 compounds with the sacrifice of some specific capacity as well as rate capacity.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The reasons for the improvement are as follows: rst of all, the a-axis expansion leads to the better cycling stability of NCMO cathode by Ce ions dopping during CeO 2 surface modication. Secondly, Mn 3+ in NCMO cathode from the charge compensation easily causes Jahn-Taller distortion during cycles, [15][16][17][18][19] which may be suppressed by proportionate CeO 2 modication. Thirdly, Mn 3+ is easy to dissolve into electrolyte during charge and discharge of the NCMO material, which is probably suppressed by optimal CeO 2 modication.…”
Section: Resultsmentioning
confidence: 99%
“…16 As Bucher and coworkers reported, 17 P2-type Na x MnO 2 and Na x Co 0.1 -Mn 0.9 O 2 were prepared in two different morphologies of hexagonal akes and hollow spheres, and the hollow spheres have higher specic capacity and the capacity retention than the akes for both doped and undoped material, and the Co-doped spheres Na x Co 0.1 Mn 0.9 O 2 exhibited a the rst discharge capacity of 183 mA h g À1 aer an initial charge capacity of 55 mA g À1 with the capacity retention of 75% aer 100 cycles and 67% at 150 cycles, and a relatively small amount of Co-dopping is benecial to suppress the structural transformations together with Na + ordering processes, as well as a positive inuence on Na + transport in the structure. Although the above Na-Mn-Co-O-based materials with low cobalt content show many advantages such as low cost, low toxicity, high safety on overcharge and high specic capacity, these materials also suffer from the large irreversible capacity loss in the initial cycle, severe capacity fading during cycling and poor rate performance like the other P2 layered oxides, resulting from phase transition and severe side reaction in a high cut-off voltage as they directly contact with electrolyte, 14,[17][18][19] which hinders their practical applications. In this regard, the signicant efforts, including cation substitution [10][11][12][13][14][15][16][17][18][19][20] and surface modication 4,18,[21][22][23][24] have been made to overcome the above drawbacks of the P2-type layered oxides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, they showed that the Mg substitution increases the diffusion coefficient of Na. In P2-Na 0.67 Mn x Co 1-x O 2 , Co-rich phases exhibit a high structural stability and superior capacity retention, whereas Mn-rich phases discharge higher capacities [57].…”
Section: P2-layered Oxide Materialsmentioning
confidence: 99%